2018
DOI: 10.1002/fam.2494
|View full text |Cite
|
Sign up to set email alerts
|

Fire‐induced reradiation underneath photovoltaic arrays on flat roofs

Abstract: The impact of the reflection of fire-induced heat from a gas burner was studied experimentally to gain knowledge on the interaction between photovoltaic (PV) panels and a fire on flat roofs. The heat flux was measured in a total of eight points at the same level as the top of the gas burner. The gas burner was placed underneath the centre of a PV panel, installed in a geometry similar to a commercial EastWest orientated mounting system, and the eight points were symmetrical pairs of two at four different dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 8 publications
6
30
0
1
Order By: Relevance
“…Next, as aforementioned, Kristensen et al have corroborated that the heat flux component from the combustible part of the PV panel contributes little to the total reradiated heat flux. Meanwhile, it was seen that the emission from the PV panel is limited to less than 1 kW/m 2 immediately after interruption of the gas flow (and thereby the almost immediate disappearance of the flame).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Next, as aforementioned, Kristensen et al have corroborated that the heat flux component from the combustible part of the PV panel contributes little to the total reradiated heat flux. Meanwhile, it was seen that the emission from the PV panel is limited to less than 1 kW/m 2 immediately after interruption of the gas flow (and thereby the almost immediate disappearance of the flame).…”
Section: Resultsmentioning
confidence: 66%
“…This study focuses on the cases in which H f is greater than H to further characterize the flame extension geometry underneath the PV panel. In previous researches on the impact of PV installation on roof fire safety, the values of h were set to about 10 cm. Therefore, h was defined as 5, 10, and 15 cm in this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four backsheets obtained respectively the best and second best reaction to fire rating on a scale with five steps. Likewise, recent parametric studies [19] have showed that the PV panel itself only contains a limited amount of combustible materials such as a thin polymer based backsheet and combustible encapsulate materials. When ignited, the materials increase the heat flux towards the subjacent roof surface for a very short period because of the thin combustible layers and thereby limited time of combustion [19].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, recent parametric studies [19] have showed that the PV panel itself only contains a limited amount of combustible materials such as a thin polymer based backsheet and combustible encapsulate materials. When ignited, the materials increase the heat flux towards the subjacent roof surface for a very short period because of the thin combustible layers and thereby limited time of combustion [19]. Given these points, the importance of the combustible materials in the main PV panel might be insignificant with respect to the propagation of the fire, -not to be mistaken with the fact that the PV panels probably are the main cause for the ignition, which leads to the fire.…”
Section: Introductionmentioning
confidence: 99%